Nonpreemptive multi-mode resource-constrained project scheduling - Andreas Drexl; Jürgen Grünewald (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1989)
This paper addresses methods for formulating and solving a general class of nonpreemptive resource-constrained project scheduling problems in which job durations are discrete functions of committed renewable, nonrenewable and doubly-constrained resources (multi-mode time resource tradeoff). We present a stochastic scheduling method with which these problems may be solved to suboptimality in an efficient way. Cumputational results demonstrate that this method is highly superior to other well-known existing deterministic scheduling rules. Extensions to problems in which job-specific (demand) resource profiles are varying with time, in addition to time-varying supply resource profiles, are discussed as well.
Keywords: 650